Indigenous knowledge of Namibia - Chinsembu, Kazhila C.; Cheikhyoussef, Ahmad; Mumbengegwi, Davis; Kandawa-Schulz, Martha; Kasanda, Choshi Darius; Kazembe, Lawrence (UNAM Press, University of Namibia, 2015)
Indigenous knowledge is the dynamic information base of a society, facilitating communication and decision-making. It is the cornerstone of many modern-day innovations in science and technology. It is also a ready and valuable resource for sustainable and resilient livelihoods, and attracts increasing public interest due to its applications in bio-technology, health, bioprospecting, pharmaceuticals, agriculture, food preparation, mathematics and astronomy. INDIGENOUS KNOWLEDGE OF NAMIBIA is a fascinating compendium aimed at a wide readership of academics and students, government officials, policy makers, and development partners. The 17 chapters examine the Indigenous knowledge of medicinal plants for treating HIV/AIDS, malaria, cancer, and other microbial infections of humans and livestock; Indigenous foods; coping and response strategies in dealing with human-wildlife conflicts, floods, gender, climate change and the management of natural resources. A new rationalisation of adolescent customary and initiation ceremonies is recommended in response to the HIV/AIDS pandemic; and a case study of the San people of Namibia speaks to the challenges of harmonising modern education with that of Indigenous people.